The Influence Of Leverage, Profitability, And Solvency On Earnings Per Share In Real Estate And Property Companies Listed On The Indonesia Stock Exchange (IDX) For The 2019–2023 Period - Agnes Vannesya; Wiliam Wiliam; Hendra Saputra (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of leverage, profitability, and solvency on earnings per share (EPS) in real estate and property companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research employs a multiple regression analysis approach, with samples taken from the financial records of companies that meet specific criteria. The findings indicate that EPS is negatively affected by leverage, whereas profitability and solvency have significantly positive impacts. These results suggest that to improve EPS, businesses must consider their capital structure and financial performance. This study is expected to assist investors and business managers in making more informed financial decisions.